HIIT produces increases in muscle power and free testosterone in male masters athletes - P Herbert; LD Hayes; NF Sculthorpe; FM Grace (Endocrine Connections, 2017)
High-intensity interval training (HIIT) improves peak power output (PPO) in sedentary aging men but has not been examined in masters endurance athletes. Therefore, we investigated whether a six-week program of low-volume HIIT would (i) improve PPO in masters athletes and (ii) whether any change in PPO would be associated with steroid hormone perturbations. Seventeen male masters athletes (60 ± 5 years) completed the intervention, which comprised nine HIIT sessions over six weeks. HIIT sessions involved six 30-s sprints at 40% PPO, interspersed with 3 min active recovery. Absolute PPO (799 ± 205 W and 865 ± 211 W) and relative PPO (10.2 ± 2.0 W/kg and 11.0 ± 2.2 W/kg) increased from pre- to post-HIIT respectively (P < 0.001, Cohen’s d = 0.32−0.38). No significant change was observed for total testosterone (15.2 ± 4.2 nmol/L to 16.4 ± 3.3 nmol/L (P = 0.061, Cohen’s d = 0.32)), while a small increase in free testosterone occurred following HIIT (7.0 ± 1.2 ng/dL to 7.5 ± 1.1 ng/dL pre- to post-HIIT (P = 0.050, Cohen’s d = 0.40)). Six weeks’ HIIT improves PPO in masters athletes and increases free testosterone. Taken together, these data indicate there is a place for carefully timed HIIT epochs in regimes of masters athletes.